Kemampuan Ibu Hamil Mengenali Tanda Bahaya Kehamilan, Persalinan dan Nifas di kelas Ibu Hamil Wilayah Kerja Puskesmas Putri Ayu Kota Jambi - Herinawati Herinawati; Lia Artika Sari; Atika Fadhilah Danaz (Universitas Baiturrahim, 2020)
AbstractPregnant mothers class to learn about health for pregnant women in the form of face-to-face in groups who want to improve the knowledge, attitudes, and skills of mothers and families regarding assessment, care, childbirth, childbirth care, illness, or situations during pregnancy-childbirth and childbirth, care newborn babies use the Mother and Child Health book (MCH) as the main ingredient. High-risk pregnant women in Puskesmas putri ayu experienced an increase in 2018 (January-December) increased by 146 high-risk pregnant women and in 2019 (January august) there were 152 high-risk pregnant women. The purpose of this study was to study the effect of education on information and communication on the ability of pregnant women to face the challenges of pregnancy, childbirth and childbirth in pregnant mothers working area of the Putri Ayu Public Health Center in 2019. The method of this study used a quasi-study with one group pretest-postet design. The sampling technique in this study was a total sampling of 50 respondents. analysis using the Wilcoxon test. Research results obtained by pregnant women p value of .000, childbirth with a p value of .000 and puerperium p value of .0009 means related to education education about health and safety for pregnant women who associate the problem of childbirth danger in the class of pregnant women at the working area of Putri Ayu Health Center Jambi in 2019. It is expected that midwives' special health centers will improve their communication skills, through health counseling, this can be used as a health workforce program in providing health education.